Description of an innovative method for the integration of robot cells with automated materials handling systems - Drávucz, Dávid; Skapinyecz, Róbert; Bányai, Tamás; Illés, Béla; Bányainé, Ágota; Tamás, Péter (Journal of Production Engineering, 2020)
The aim of this publication is to present a process development method that enables the integration of automated material handling systems and robotic workstations in an innovative way. Given that, in line with the spread of the Industry 4.0 concept, the robotization of production is playing an increasingly important role today, the significance of such methods is constantly on the rise. This is well illustrated by the example of a possible application discussed in the article.